Laser irradiation in water for the novel, scalable synthesis of black TiOx photocatalyst for environmental remediation - Zimbone, Massimo; Cacciato, Giuseppe; Boutinguiza, Mohamed; Privitera, Vittorio; Grimaldi, Maria Grazia (Beilstein Journal of Nanotechnology, 2017)
Since 1970, TiO2 photocatalysis has been considered a possible alternative for sustainable water treatment. This is due to its material stability, abundance, nontoxicity and high activity. Unfortunately, its wide band gap (≈3.2 eV) in the UV portion of the spectrum makes it inefficient under solar illumination. Recently, so-called “black TiO2” has been proposed as a candidate to overcome this issue. However, typical synthesis routes require high hydrogen pressure and long annealing treatments. In this work, we present an industrially scalable synthesis of TiO2-based material based on laser irradiation. The resulting black TiOx shows a high activity and adsorbs visible radiation, overcoming the main concerns related to the use of TiO2 under solar irradiation. We employed a commercial high repetition rate green laser in order to synthesize a black TiOx layer and we demonstrate the scalability of the present methodology. The photocatalyst is composed of a nanostructured titanate film (TiOx) synthetized on a titanium foil, directly back-contacted to a layer of Pt nanoparticles (PtNps) deposited on the rear side of the same foil. The result is a monolithic photochemical diode with a stacked, layered structure (TiOx/Ti/PtNps). The resulting high photo-efficiency is ascribed to both the scavenging of electrons by Pt nanoparticles and the presence of trap surface states for holes in an amorphous hydrogenated TiOx layer.
Keywords: black titania; laser irradiation in water; photocatalysis; TiOx; water treatment